An analysis of outdoor advertising apparel using semiotics approach - Agcaoili, Junelyn Alexis; Mayo, Adelaida Villaraza (2003.)
This is a descriptive research which discussed the analysis of advertising for clothing here in the Philippines - specifically print advertisements in the forms of billboards by local retailers of women's clothes from teen to young adult. Likewise, it explored the process involved in making these advertisements, and the factors that affected the creation of these ads. The writer conducted a series of interviews with the people concerned with marketing and advertising of Kamiseta, Plains & Prints, Folded & Hung, BA-YO and Freeway. These local retail stores have been actively promoting their designs in billboards, local magazines, radio ads and TV commercials. These brands targeted toward the young adult market. The researcher also interviewed some members of the creative department of McCann Ericsson, a known advertising firm experienced with handling clothing companies. This study made an attempt to relate the mechanics in the making of billboard ads of local fashion brands that cater to young women. It aimed to discuss why more and more companies are choosing this kind of medium - billboards - to advertise their products. The word "analysis" pertains only to the conceptualization process in creating the billboard advertisements. Specifically, the study discussed how companies commissioned ad agencies to translate the "image" that they want to project in relation to the women's apparel that they are selling. The study may serve as a model or guide to future or similar studies about fashion advertising. Also, this type of research topic will support the competency of the Clothing Technology program. It offers a view of the field of fashion advertising and promotion. CT graduates will be able to familiarize themselves with the variety of career opportunities that the fashion industry provides. The study had gathered that the "Filipino standards of beauty" influenced by the "western standards of beauty" in which chiseled narrow faces are considered to be very attractive and much preferred by people to endorse their products. The results of the study inferred that all billboards portrayed the Filipinos most common notion of beauty which is the meztiza. Since most Filipinos are brown-skinned, women who are very fair are considered beautiful. Likewise, the characteristics of all the billboards showed a popular meztiza beauty as their image model projecting sweetness and confidence combined. Th models chosen for the billboard ads happened to be celebrities, admired for their beauty and talent. The researcher had used "semiotics" to interpret the signs and symbols for these billboards. The 5 billboard brands had different endorsers and have different reasons for picking these endorsers and several reasons in choosing the colors to use for the billboards. The expressions and the poses of the models conveyed meanings that were used to attract passersby. The study found out that all of the ads used campaign that was unique, versatile and one that would leave consumers intrigued - and hopefully loyal followers of the brand. The study utilized purposive sampling method because its main focus was on young women's apparel, and the chosen informants were from clothing brands that cater to this group. It is hoped that future studies will lead to more discussions on different forms of print media and other types of women's apparel. Also, it would be interesting to research on men's apparel and what type of image clothing companies want to project.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Advertising -- Clothing and dress -- Philippines; Advertising, Outdoor